Abnormal Head Posture in Unilateral Superior Oblique Palsy. Issue 1 (2nd January 2021) - Khorrami-Nejad, Masoud; Akbari, Mohamad Reza; Kangari, Haleh; Akbarzadeh Baghban, Alireza; Masoomian, Babak; Ranjbar-Pazooki, Mahsa
ABSTRACT: Purpose : To evaluate the manifestations and severity of abnormal head posture (AHP) in unilateral congenital and acquired superior oblique palsy (SOP) patients and to assess the effect of AHP on facial appearance. Patients and methods : This case series study was performed on 60 consecutive SOP patients, which consisted of 47 patients with congenital SOP and 13 patients with the acquired source. The exact type of AHP in congenital and acquired cases was determined based on direct observation. In addition, a close-up picture from 40 cm with habitual AHP was captured from all patients. For evaluation of the severity of AHP and measurement of head tilt, these pictures were analyzed by the Corel Draw X7 software (Corel Corp, Canada). Besides, qualitative and quantitative facial asymmetry parameters were evaluated by the assessment of pictures of patients, which were taken in different gazes. Results : Five different manifestations of AHP were observed to the contralateral side of the palsy; 1 – pure head tilt, 2 – simultaneous head tilt and turn, 3 – pure head turn, 4 – head tilt and chin down, and 5 – head tilt and turn with chin down. The frequency of these five manifestations of AHP in the congenital group were 23 (48.9%), 10 (21.3%), 4 (8.5%), 5 (10.6%), and 5 (10.6%) patients, respectively ( P <.001) and in acquired patients, were 1 (7.7%), 8 (61.5%), 2 (15.4%), 2 (15.4%), and 0 (0%), respectively ( P =.024). In all SOP patients, the most common manifestations of AHP were pure head tilt (40%), simultaneous head tilt and turn (30%), and head tilt with chin down (11.7%), respectively. The mean degrees of head tilt in congenital and acquired patients were 15.10° ± 9.34° and 9.61° ± 5.84°, respectively ( P =.022). Conclusion : The most common type of AHP in congenital SOP patients was contralateral head tilt, but in acquired cases was simultaneous head tilt and turn. The mean amount of head tilt in the acquired group was significantly higher than congenital patients; in contrast, the frequency of facial asymmetry was higher in the congenital group compared with the acquired patients.